MINDS UNVEILED exploring the effects of generative AI on business behavior. - Rodriguez, Raul V.; K., Hemachandran ([S.l.] : PRODUCTIVITY PRESS, 2024)
This book demonstrates how generative AI, a form of sophisticated AI technology, is transforming our knowledge of how the human mind functions in relation to business leadership and decision-making. It describes the most recent findings and applications of generative AI in psychology.
19. Radiant Horizons of Augmented Reality and Virtual Reality in Customer-Centric Choices for Products: Artificial Intelligence (AI) Solutions Path to Fueling Business Towards Innovation Vague Futuristic Approach -- Index
Keywords: Artificial intelligence -- Economic aspects; Information technology -- Management; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management